Ontological Assumptions in Techno-Anthropological Explorations of Online Dialogue through Information Systems. - Otrel-Cass, Kathrin; Andrule, Kristine (Techné: Research in Philosophy & Technology)
With the widespread infusion of online technology there has been an increase in various studies investigating the practices in online communities including also philosophical perspectives. What those debates have in common is that they call for more critical thinking about the theory of online communication. Drawing on Techno-Anthropological research perspectives, our interest is placed on exploring and identifying human interactions and technology in intersectional spaces. This article explores information systems that allow for interchanges of different users. We discuss ontological assumptions that focus on understanding the kind of dialogue that can be captured between different expert groups when they utilize information systems. We present the notion of 'dialogic' by Mikhail Bakhtin and contextualize it through an analysis of online dialogue. Dialogic or 'conversation and inquiry' is discussed as being mediated through human relationships. Acknowledging the existence of at least two voices the underlying differences between dialogue partners are highlighted.